Pulmonary functions and respiratory symptoms of the women exposed to mine tailings - Usha G Shenoy; Karthiyanee Kutty (Wolters Kluwer Medknow Publications, 2020)
Introduction: Impact of mining on environmental degradation affecting water, soil, and air is established. With the recognition that air pollution is the most important cause for noncommunicable cause for mortality and women as a gender at higher susceptibility to lung dysfunction, it was necessary to make a start to understand the detrimental effect of mine tailing on ambient air pollution almost two decades after closure and its effect on the vulnerable women residents. Materials and Methods: After institutional ethical clearance and informed consent, 258 females between the age of 18 and 60 years living in the gold mining town for over 3 years were selected. Respiratory symptoms were assessed using the American Thoracic Society questionnaire and lung functions of forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), peak expiratory flow rate (PEFR), and FEV1/FVC% using computerized spirometer. Dust samples were analyzed for particulate matter concentration (PM) by gravimetric method. Results: The average PM concentration in the mining area was 1.491±0.737 mg/m. Of the respiratory symptoms, complaints of cough were 34%, breathlessness 31%, phlegm 30%, and asthma 20%. FVC, FEV1, and PEFR were 1.3157 ± 0.487 L/s, 1.2500 ± 0.4850 L/s, and 2.611 ± 1.185 L/s, respectively. FEV/FEV1 was 93.650 ± 9.2733%. Conclusion: Mine tailing contributed to ambient air pollution, which has significantly decreased lung functions in the local women residents and produced the restrictive type of lung abnormality.